Эллипсис в словенском и русском языках - Михайловна Коницкая, Елена (Slavistica Vilnensis, 2003)
The paper is a contrastive analysis of ellipsis in Slovenian and Russian. The comparison is conducted within the framework of the Russian Grammar 80 syntax theory, which distinguishes between consituationally conditioned and unconditioned structural sentence schemes. Both Slovenian and Russian allow ellipsis of various parts of a sentence.The conditions for ellipsis (congruity of sentence structure and repetition of elements) are also similar in Slovenian and Russian.In consituational dependent incomplete realizations in Slovenian and Russian, differences are observed in the specification of the predictive element. In elision in negation, Slovenian preserves the negative particle, in contrast to Russian. Moreover, in Russian, ellipsis of subject-object determinants expressed as pronouns is common, whereas in Slovenian, determinants generally are retained.Ellipsis within a phrase is characterized in both languages by omission of basic words: the differences are associated with the degree of acceptability in the language of corresponding (equivalent) compound names, or they are usually strengthened. Differences are observable also in ellipsis of a subordinate word from prepositional phrases in which the the preposition is retained. Incomplete ellipse of predicate and subject-object determinants is discussed separately.The variety of Slovenian verb forms allows the preservation within the sentence structure of formal predicate indicators, in contrast to Russian, where this type of construction is much less common. Anaphorization of object-subject determinants in Slovenian demonstrates the importance to the language of a semantically more split sentence structure.The differences in ellipsis between the languages are also based on the interpretation of similar sentences as consituationally unconditioned incomplete realizations in one language, and as full realizations in the other. Similarities and differences are also examined with respect to lexico-semantic groups of verbs that act as predicates in both languages in consituationally unconditional sentence structures.